Modernity and capitalism (15 theses) - Echeverría, Bolívar (Quilmes, Argentina : Universidad Nacional de Quilmes, 2005)
The author study in this essay the great problem of characterization of the main elements of this enormous mankind project, living in the last five centuries, who is the capitalist modernity. From Marx¿s perspectives, the text reconstruct some of the central evolutive lines of this modernity, as productivism, individualism, progressism, and so on, and the four principal ¿ethos¿ of this same capitalist modernity.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Descripción basada en Revista theomai, n. 11 (primer semestre 2005), P. 25 sin numerar.
Recurso electrónico. Santa Fe, Arg.: elibro, 2023. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Capitalismo; Modernidad capitalista; Modernidad; Artículos electrónicos.